2021
DOI: 10.1038/s41389-021-00372-5
|View full text |Cite
|
Sign up to set email alerts
|

Cdk5 drives formation of heterogeneous pancreatic neuroendocrine tumors

Abstract: Pancreatic neuroendocrine tumors (PanNETs) are a heterogeneous population of neoplasms that arise from hormone-secreting islet cells of the pancreas and have increased markedly in incidence over the past four decades. Non-functional PanNETs, which occur more frequently than hormone-secreting tumors, are often not diagnosed until later stages of tumor development and have poorer prognoses. Development of successful therapeutics for PanNETs has been slow, partially due to a lack of diverse animal models for pre-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…ccCDKs are key regulators of cell cycle progression and transcription. Previous studies also provided evidences supporting the oncogenic potential of CDK3 and CDK5 in skin tumorigenesis and pancreatic neuroendocrine tumors, while an increase in CDK7 expression is related to a poorer overall survival and disease-free survival in squamous cell carcinomas of the head and neck [ 21 , 22 , 23 ]. At present, there are no systematic and comprehensive studies on ccCDK family genes.…”
Section: Discussionmentioning
confidence: 97%
“…ccCDKs are key regulators of cell cycle progression and transcription. Previous studies also provided evidences supporting the oncogenic potential of CDK3 and CDK5 in skin tumorigenesis and pancreatic neuroendocrine tumors, while an increase in CDK7 expression is related to a poorer overall survival and disease-free survival in squamous cell carcinomas of the head and neck [ 21 , 22 , 23 ]. At present, there are no systematic and comprehensive studies on ccCDK family genes.…”
Section: Discussionmentioning
confidence: 97%
“…Carter A.M. et al developed a bi-transgenic mouse line in which the aberrant activation of the cyclin-dependent kinase 5 (Cdk5) pathway can selectively induce the growth of pancreatic β-cells with consequent generation of heterogeneous population of NETs [ 106 ]. The utility of this model is enhanced by the ability to form tumor-derived allografts in a large cohort of animals.…”
Section: Future Development Of Preclinical Models In Carcinoid Syndromementioning
confidence: 99%
“…It may represent the starting point for the development of innovative transgenic mouse models of midgut and bronchial NETs with CS, for example, through the transgenic overexpression of TPH-1 promoter mediated by the activation of Cdk5 pathway. Indeed, this pathway seems to be involved in the tumorigenesis of several NETs [ 106 , 107 ].…”
Section: Future Development Of Preclinical Models In Carcinoid Syndromementioning
confidence: 99%
“…The incidence of pNENs has risen considerably in recent decades, accounting for over 3% of pancreatic malignancies, due to advancements in diagnostic methods 2 . Notably, recent research has revealed several potential novel biomarkers, such as INSM1 and CDK5, and implicated some new signaling pathways, including TGF‐beta and the NOTCH pathway, as being relevant to the tumorigenesis of pNENs 3–6 . Despite these advances, current treatment options for the medical management of pNENs remain limited in their sensitivity and specificity.…”
Section: Introductionmentioning
confidence: 99%